Pengaruh Faktor Sosial Ekonomi Terhadap Pendapatan Usahatani Padi di Kelurahan Allepolea Kecamatan Lau Kabupaten Maros - Nur Indah Sari; Arifin Arifin; Abd. Asis Pata (Jurnal Agribis, 2024)
This research was conducted in Allepole Village, Lau District, Maros Regency. This location was chosen because the majority of the people are farmers and have been cultivating rice for a long time. The aims of this study were (1) to find out how much rice farming income was in Allepolea Village, Lau District, Maros Regency, (2) to determine the effect of socio-economic factors on rice farming income in Allepolea Village, Lau District, Maros Regency. The data used are primary data, namely data collected directly from the field, and secondary data, namely data obtained from literature studies from various sources that can be used as references in this study. Sampling used the Slovin formula with an error rate of 15% to obtain 40 samples, using the simple random sampling method. Data collection was carried out through survey results using a questionnaire and then tabulated to obtain data for analysis purposes. The data analysis used was cost analysis (TC=FC+VC), revenue (TR=Q×P), income (Pd=TR-TC), and used multiple linear regression analysis for the second problem. The results of this study obtained an average income of rice farming in Allepolea Village, Lau District, Maros Regency Rp. 5,094,568.75 with a total receipt of Rp. 8,284,562.5 and production costs Rp. 3,189,993.75. Farmer's age (X1), education level (X2) and land area (X4) have an effect on rice farming income, while farming time (X3) has no effect.